A Room‐Temperature Ferroelectric Resonant Tunneling Diode. Issue 35 (2nd August 2022) - Ma, Zhijun; Zhang, Qi; Tao, Lingling; Wang, Yihao; Sando, Daniel; Zhou, Jinling; Guo, Yizhong; Lord, Michael; Zhou, Peng; Ruan, Yongqi; Wang, Zhiwei; Hamilton, Alex; et al.
Abstract: Resonant tunneling is a quantum‐mechanical effect in which electron transport is controlled by the discrete energy levels within a quantum‐well (QW) structure. A ferroelectric resonant tunneling diode (RTD) exploits the switchable electric polarization state of the QW barrier to tune the device resistance. Here, the discovery of robust room‐temperature ferroelectric‐modulated resonant tunneling and negative differential resistance (NDR) behaviors in all‐perovskite‐oxide BaTiO3 /SrRuO3 /BaTiO3 QW structures is reported. The resonant current amplitude and voltage are tunable by the switchable polarization of the BaTiO3 ferroelectric with the NDR ratio modulated by ≈3 orders of magnitude and an OFF/ON resistance ratio exceeding a factor of 2 × 10 4 . The observed NDR effect is explained an energy bandgap between Ru‐t2g and Ru‐eg orbitals driven by electron–electron correlations, as follows from density functional theory calculations. This study paves the way for ferroelectric‐based quantum‐tunneling devices in future oxide electronics. Abstract : Robust room‐temperature ferroelectric modulated resonant tunneling and negative differential resistance (NDR) behaviors under external voltage in perovskite oxide BaTiO3 /SrRuO3 /BaTiO3 quantum‐well structures are reported. The NDR ratio can be modified by ≈3 orders of magnitude, depending on the polarization states of the ferroelectric barrier, and a large OFF/ON resistance ratio up to 23 000 is obtained.